Multimodal Construction of Emotional Meaning in Animated Storytelling: Language and Visual Representation in Inside Out - Cahyani, Anisa Putri; Tsurayya, Ghaitsa (UICELE, 2026)
Animated films are multimodal texts that construct meaning through the combination of language, visuals, movement, music, and sound effects. Among contemporary animated films, Inside Out (Pixar Animation Studios, 2015) yields a compelling representation of emotional responses by personifying Joy, Sadness, Anger, Fear, and Disgust as characters that govern emotional experiences. This study examines how emotional meaning is constructed through the interaction of verbal and visual modes in Inside Out. Employing a qualitative descriptive design, the research adopts Multimodal Discourse Analysis (MDA) as its conceptual framework to examine selected scenes from the film. The analysis focuses on dialogue, colour symbolism, character design, facial expressions, body movement, camera framing, and visual composition as linked semiotic resources. Data were collected from the film's screenplay and corresponding visual sequences to explore how linguistic and visual elements collaboratively communicate emotional experiences. The findings disclose that emotional meanings emerge through the combination of multiple semiotic resources rather than through spoken language alone. Visual elements such as colour palettes, gesture, gaze, and spatial arrangement reinforce the emotional value conveyed in dialogue, enabling audiences to discern complex psychological states more effectively. Furthermore, the film demonstrates how multimodal storytelling facilitates emotional involvement by combining verbal narration with symbolic visual representation. The study adds to multimodal discourse studies by showing how animated films function as sophisticated multimodal texts and point out the importance of multimodal literacy in understanding contemporary audiovisual communication.